Failed Diplomacy : The Tragic Story of How North Korea Got the Bomb - Pritchard, Charles L. (Book collections on Project MUSE., 2007)
"Offers an insider's analysis of developments on the Korean peninsula and how North Korea was able to develop nuclear weapons. Provides a first-hand account of how the Six-Party Talks were initiated, with a step-by-step review of each round of negotiations, detailing the national interests of the key players"--Provided by publisher